Calculation of shielding performance of CRT concrete for proton therapy and optimal shielding design of treatment delivery room. (November 2022) - Gao, Han; Chen, Long; Tang, Bo; Wang, Yidi; Du, Chuansheng; Liu, Kun; Qiu, Dong; Kong, Xianghui; Yang, Bing; Yin, Yuchen; Zhang, Wenyue; Tu, Yu; et al.
Abstract: Proton therapy is becoming increasingly popular worldwide, and its shielding must be considered. The cathode ray tube (CRT) material is a glass containing heavy metal elements, these materials have become a good choice for the production of radiation-proof concrete. In this study, the ability of concrete containing CRT fragments as shielding materials for proton therapy rooms is evaluated in terms of neutron shielding ability, neutron reflection ability, ambient dose equivalent rate, and induced radioactivity. In addition, this concrete is compared with commonly used ordinary concrete, boron-containing concrete, and barite concrete. The results show that with the increase of CRT content (10%–90%), the transmitted neutron fluence decreases continuously (5.06 × 10 −10 – 1.77 × 10 −10 cm −2 /particle), and the reflection of neutrons gradually increases (2.64 × 10 −9 – 3.20 × 10 −9 cm −2 /particle), resulting in an increased potential to patients. When 50% CRT concrete is used, the ambient dose equivalent rate is below 3.80 μSv/h/nA, and 90% CRT concrete is below 3.11 μSv/h/nA. The trend of radionuclide activity of induced radioactivity from 0 to 60 min after irradiation for concrete with different CRT contents is 2.74–5.38 × 10 −3 Bq/cm 3, and the maximum photon fluence is 8.13 × 10 2 cm −2 . In conclusion, the optimization model of the three-layer shielding structure of ordinary concrete, high CRT content concrete, and boron-containing concrete is proposed with ambient dose equivalent rate less than 1.88 μSv/h/nA, minimizing the reflected neutrons to which the patient is exposed. This study shows the protection performance of CRT concrete is better than ordinary concrete and barite concrete. Highlights: The ability of CRT concrete as a shielding materials for proton therapy is evaluated and compared. Neutron shielding and reflection ability, ambient dose equivalent rate, induced radioactivity are considered. The optimization model of the three-layer shielding structure is proposed.